The Inculturation of Religion and Culture in the Use of Trade Charms at Tanjung Bajure Market, Sungai Penuh City - Satria, Oga; Pratama, M. Raditya Ridho (Ishlah: Jurnal Ilmu Ushuluddin, Adab dan Dakwah, 2025)
This study examines the phenomenon of using Quranic verses as trade charms in Sungai Penuh City through the Living Qur'an approach, which highlights how the community interprets and applies sacred texts in the local economic context. This research employs a qualitative method with a phenomenological and reception approach to understand the meanings, beliefs, and perspectives of the community regarding this practice. Data were collected through in-depth interviews, observations, and literature studies. The findings indicate that the use of Quranic verses as trade charms stems from various motivations, ranging from the belief in blessings to efforts to attract customers. Community views on this practice are divided: some regard it as a legitimate effort as long as it aligns with Islamic teachings, while others see it as an abuse of sacred texts. The study also reveals a contestation between customary and religious authorities in assessing the legitimacy of this practice. This research aims to contribute to a deeper understanding of the relationship between local traditions, Islamic values, and community economic practices. Additionally, it opens a space for theological reflection on the use of religious symbols in economic contexts. Penelitian ini mengkaji fenomena penggunaan ayat-ayat al-Qur'an sebagai penglaris dagangan di Kota Sungai Penuh, dengan menyoroti praktik masyarakat dalam memaknai dan menerapkan ayat-ayat suci dalam konteks ekonomi lokal. Penelitian ini menggunakan metode kualitatif dengan pendekatan fenomenologi dan resepsi untuk memahami makna, keyakinan, dan pandangan masyarakat terkait praktik tersebut. Data diperoleh melalui wawancara mendalam, observasi, dan studi literatur. Hasil penelitian menunjukkan bahwa penggunaan ayat-ayat al-Qur'an sebagai penglaris memiliki latar belakang yang beragam, mulai dari keyakinan akan keberkahan hingga upaya menarik pelanggan. Pandangan masyarakat terhadap praktik ini terbagi menjadi dua: sebagian menganggapnya sebagai bentuk usaha yang sah selama tidak menyimpang dari ajaran Islam, sementara yang lain melihatnya sebagai bentuk penyalahgunaan ayat-ayat suci. Penelitian ini juga menemukan adanya kontestasi antara otoritas adat dan agama dalam menilai legitimasi praktik tersebut. Penelitian ini diharapkan dapat memberikan kontribusi dalam membangun pemahaman yang lebih mendalam mengenai hubungan antara tradisi lokal, nilai-nilai Islam, dan praktik ekonomi masyarakat. Selain itu, penelitian ini juga membuka ruang diskusi untuk refleksi teologis tentang penggunaan simbol-simbol agama dalam konteks ekonomi.